Production of Neoagaro-Oligosaccharides With Various Degrees of Polymerization by Using a Truncated Marine Agarase - Qu, Wu; Wang, Dingquan; Wu, Jie; Chan, Zhuhua; Di, Wenjie; Wang, Jianxin; Zeng, Runying (Frontiers in Microbiology, 2020)
The bioactivities of marine neoagaro-oligosaccharides (NAOS) with the degree of polymerizations (DPs) of 4–12 have been proven, such as fresh-keeping, whitening, and prebiotics. However, NAOSs produced by most marine β-agarases always possess low DPs (≤ 6) and limited categories; thus, a strategy that could efficiently produce NAOS especially with various DPs ≥ 8 must be developed. In this study, 60 amino acid residues with no functional annotation result were removed from the C-terminal of agarase AgaM1, and truncated recombinant AgaM1 (trAgaM1) was found with the ability of producing NAOS with various DPs (4–12) in some certain conditions. The catalytic efficiency and stability of trAgaM1 were obviously lower than the wild type (rAgaM1), which probably endowed trAgaM1 with the ability of producing NAOS with various DPs. The optimum conditions for various NAOS production included mixing 1.0% agarose with 10.26 U/mL trAgaM1 and incubation at 50 °C in deionized water for 100 min. This strategy produced NAOS with DPs of 4–12 at a high yield (2.23 × 104 μmol/L) and substrate utilization rate (92.5%), and these NAOS served as the end-products of the reaction. The conditions for trAgaM1 expression in a shake flask and 5 L fermentation tank were optimized, and the yields of trAgaM1 increased by 56- and 842-folds compared with those before optimization, respectively. This work provides numerous substrate sources for production and activity tests of NAOS with high DPs, and offers foundation for large-scale production of NAOS with various DPs at a low cost.